Development of a Non-ionic Surfactant Derived from High Oleate Ester for EOR Application - LEE, SUSAN YUN CHING (2013)
Natural oil as an alternative raw material to petroleum fractions for various applications have been given much attention due to the fluctuation of global oil price and increasing environmental issues. In this research, a nonionic surfactant has been synthesized successfully using raw material from natural resources namely oleate ester. The synthesized surfactant was characterized and developed to possess properties that makes it suitable for EOR applications in Malaysia. The major properties that were addressed were the surfactant's ability to tolerate harsh conditions of high temperature and high salinity (more than 100°C and 35000 ppm respectively); and to generate stable foam in the presence of oil to make it a suitable candidate for gas mobility control. These were achieved by blending the synthesized surfactant with two additives - an anionic surfactant (sodium dodecyl sulfate) and a foam booster. The formulation of blended surfactants was found to be stable at 100°C, compatible with high salinity and produced foams that are stable in the presence of oil. vn